Oxidative Spin-Spray-Assembled Coordinative Multilayers as Platforms for Capacitive Films - Salomäki M; Marttila L; Kivelä H; Tupala M; Lukkari J (AMER CHEMICAL SOC, 2022)
The spin-spray-assisted layer-by-layer (LbL) assembly technique was used to prepare coordinative oxidative multilayers from Ce(IV), inorganic polyphosphate (PP), and graphene oxide (GO). The films consist of successive tetralayers and have a general structure (PP/Ce/GO/Ce)(n). Such oxidative multilayers have been shown to be a general platform for the electrodeless generation of conducting polymer and melanin-type films. Although the incorporation of GO enhances the film growth, the conventional dip LbL method is very time consuming. We show that the spin-spray method reduces the time required to grow thick multilayers by the order of magnitude and the film growth is linear from the beginning, which implies a stratified structure. We have deposited poly(3,4-ethylenedioxothiophene), PEDOT, on the oxidative multilayers and studied these redox-active films as models for melanin-type capacitive layers for supercapacitors to be used in biodegradable electronics, both before and after the electrochemical reduction of GO to rGO. The amount of oxidant and PEDOT scales linearly with the film thickness, and the charge transfer kinetics is not mass transfer-limited, especially after the reduction of GO. The areal capacitance of the films grows linearly with the film thickness, reaching a value of ca. 1.6 mF cm(-2) with 20 tetralayers, and the specific volumetric (per film volume) and mass (per mass of PEDOT) capacitances are ca. 130 F cm(-3) and 65 F g(-1), respectively. 5,6-Dihydroxyindole can also be polymerized to a redox-active melanin-type film on these oxidative multilayers, with even higher areal capacitance values.